The critique of management toward a philosophy and ethics of business management - Blok, Vincent 1970- (Routledge, 2022)
"This book reflects on the nature of business management to contribute to the development of a philosophy and ethics of management. It engages in conceptual engineering of management to delineate the phenomenon of management and, as a result, to open a new perspective on management beyond its self-evident conceptualization. After questioning the self-evident concept of management, the author develops a philosophy of management with six dimensions of the nature of management: management as participation; management as resistance and responsive action; management as constitution of meaning; management as politico-economic governance; management as non-reductive stakeholder engagement; and management as epistemic insufficient entrepreneurship. These six dimensions of management are taken as points of departure to develop an integrated concept of business ethics, an individual competence for ethical business management, and a concept of ethical codes for corporate social responsible behavior. This new conception of philosophy of management and business ethics can guide future philosophical and empirical work on the nature of management. The Critique of Management is an excellent resource for researchers, students, and professionals interested in philosophy of management, business ethics, and corporate social responsibility"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on December 03, 2021)
Keywords: Industrial management -- Philosophy; Management -- Philosophy; Business ethics; Social responsibility of business; Gestion d'entreprise; Philosophie; Gestion; Philosophie; Morale des affaires; Entreprises; Responsabilité sociale; BUSINESS & ECONOMICS / Management; PHILOSOPHY / Ethics & Moral Philosophy; Industrial management; Philosophy; Management; Philosophy